EFFECT OF CIRCUIT TRAINING IN OSTEOARTHRITIS OF KNEE - Bhagat, Pallavi; Jagtap, Vaishali; T, Poovishnu Devi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: The objective of the study is to find the effect of circuit training on quality of life. To find the effect of conventional therapy (interferential therapy [IFT] and isometric exercise) and to find the effect of conventional therapy with or without circuit training in OA knee. Methods: A total of 30 participants of 50-60 years of age, having osteoarthritis (OA) knee were recruited and allocated into two groups and treated with IFT, exercises, and circuit training for 4 weeks. Pre- and post-intervention outcome were measured using Western Ontario and McMaster University OA Index (WOMAC) and visual analog scale (VAS). Result: Both groups showed improvement, but there was an extremely significant improvement on VAS and WOMAC scales in the group treated with circuit training along with conventional treatment (IFT and isometric exercises). Conclusion: From this study, we conclude that circuit training along with IFT and isometric exercises shows an extremely significant effect over IFT and isometric exercises alone in OA knee patients.